National HIV programme testing recommendations - Chiaw Yee Choy; Chen Seong Wong; P Arun Kumar; Raymond Tzer Pin Lin; Carmen Low; Matthias Paul Han Sim Toh; Flora Huang; Dariusz Piotr Olszyna; Yii Ean Teh; Mei Fong Jaime Chien; Sophia Archuleta (Singapore Medical Journal)
In recognition of the morbidity and mortality associated with human immunodeficiency virus (HIV), the Joint United Nations Programme on HIV/acquired immunodeficiency syndrome (AIDS) (UNAIDS) aims to end the epidemic by setting and striving to achieve the ambitious 95–95–95 targets. However, Singapore is still not performing well in the first UNAIDS target. The National HIV Programme (NHIVP) developed this set of recommendations based on an adaptation of major international guidelines from the World Health Organization and the US Centers for Disease Control and Prevention. The goals of this recommendation are: (1) to increase the uptake of HIV testing; (2) to allow earlier detection and identification of individuals with unrecognised HIV infection; (3) to facilitate linkage to clinical services; and (4) reduce further transmission of HIV infection in Singapore.